Undergraduate nursing student knowledge and attitudes of healthcare consumers with problematic alcohol and other drug use: A scoping review. (7th August 2021) - Smyth, Darren; Wilson, Cate; Searby, Adam
Abstract: Problematic alcohol and other drug use has a significant societal, personal, and financial burden. Nurses are key in responding to problematic alcohol and other drug use; however, research indicates many nurses hold negative attitudes towards people with substance and alcohol use disorders. Further, little content exists in most undergraduate degrees to address stigma held by new nurses. The objective of this scoping review, structured using Arksey and O'Malley's (International Journal of Social Research Methodology: Theory and Practice, 8 (1), 19–32, 2005) framework, is to examine studies that either explore or attempt to improve the knowledge and attitudes of undergraduate nurses caring for people who use alcohol and other drugs. Our initial search located 610 articles, and after screening, 14 articles were appraised using the Mixed Methods Appraisal Tool (MMAT) and included in this review. Most of the papers appraised were small, localized studies using evaluation methods considered low quality, but showed promising results in addressing stigma and confidence in providing care to people who use alcohol and other drugs. This review indicates that a consistent direction for improving knowledge and attitudes among undergraduate nursing students working with people who use alcohol and other drugs is urgently needed. Further studies of interventions, tested with more rigorous evaluation methodologies, are required to extend existing work in this area.